2022
DOI: 10.3390/su142316291
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Sulphur Dioxide (SO2) Quality Levels of Jeddah City Using Machine Learning Approaches with Meteorological and Chemical Factors

Abstract: Modeling air quality in city centers is essential due to environmental and health-related issues. In this study, machine learning (ML) approaches were used to approximate the impact of air pollutants and metrological parameters on SO2 quality levels. The parameters, NO, NO2, O3, PM10, RH, HyC, T, and P are significant factors affecting air pollution in Jeddah city. These factors were considered as the input parameters of the ANNs, MARS, SVR, and Hybrid model to determine the effect of those factors on the SO2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Zhang and Goh [41] applied MARS to predict pile drivability, and their study showed that MARS is more efficient than BPNN. In addition to engineering, MARS has also been applied in air pollution modeling [13], geotechnical engineering [42], and solar and renewable energy [14].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang and Goh [41] applied MARS to predict pile drivability, and their study showed that MARS is more efficient than BPNN. In addition to engineering, MARS has also been applied in air pollution modeling [13], geotechnical engineering [42], and solar and renewable energy [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, the relationship between air pollution, labor insurance, and their combined impact on productivity has received insufficient attention, despite labor insurance playing a vital role in enhancing productivity [9][10][11]. To bridge these knowledge gaps, this study employs state-of-the-art machine learning techniques renowned for their exceptional predictive capabilities and capacity to model nonlinear relationships [12][13][14], particularly among air pollution, labor insurance, other economic factors, and labor productivity.…”
Section: Introductionmentioning
confidence: 99%